Pain in axial spondyloarthritis: role of the JAK/STAT pathway - Selmi, Carlo; Chimenti, Maria Sole; Novelli, Lucia; Parikh, Bhumik K.; Morello, Francesca; de Vlam, Kurt; Ciccia, Francesco (Frontiers in Immunology, 2024)
Axial spondyloarthritis (axSpA) is a chronic inflammatory disease that is characterized by new bone formation in the axial musculoskeletal system, with X-rays discriminating between radiographic and non-radiographic forms. Current therapeutic options include non-steroidal anti-inflammatory drugs and in addition to biological disease modifying anti-rheumatic drugs that specifically target tumor necrosis factor-alpha (TNFα) or interleukin (IL)-17. Pain is the most critical symptom for axSpA patients, significantly contributing to the burden of disease and impacting daily life. While the inflammatory process exerts a major role in determining pain in the early phases of the disease, the symptom may also result from mechanical and neuromuscular causes that require complex, multifaceted pharmacologic and non-pharmacologic treatment, especially in the later phases. In clinical practice, pain often persists and does not respond further despite the absence of inflammatory disease activity.Cytokines involved in axSpA pathogenesis interact directly/indirectly with the Janus kinase (JAK)/signal transducer and activator of transcription (STAT) signalling cascade, a fundamental component in the origin and development of spondyloarthropathies. The JAK/STAT pathway also plays an important role in nociception and new generation of JAK inhibitors have demonstrated rapid pain relief. We provide a comprehensive review of the different pain types observed in axSpA and the potential role of JAK/STAT signalling in this context, with a specific focus on data from preclinical studies and data from clinical trials with JAK inhibitors.